INVESTIGATING AIRFLOW PATTERNS NEAR SUPPLY AND EXHAUST VENTS OF ROOMBASED VENTILATION UNIT USING LASER DOPPLER ANEMOMETRY - Simson, Raimo; Annus, Ivar; Mikola, Alo; Koiv, Teet-Andrus (European Scientific Journal, ESJ, 2014)
In this study, airflow patterns near side-to-side located supply andexhaust vents of a duct-less room-based ventilation unit with recuperativecross-flow plate heat exchanger were investigated. Airflow fields werecreated by measuring a grid of 550x550mm with 50mm steps on five verticalplanes with a distance of 50mm between the steps. The mean velocitycomponents were measured using two-component laser Doppler anemometry(LDA). Although the airflow patterns indicate short-circuiting of the airflowsnear the supply and exhaust vents, it can be considered marginal and shouldbe accounted only at low flow rates. It is noted that the supply air jet, due tothe Coanda effect, is attracted to the external wall, thus extending the throwdistance of the jet. The information gathered in this experiment can be usedin future research, i.e. to validate numerical CFD models used for estimatingventilation effectiveness, thermal comfort, contaminant concentration etc.,and to determine the suitability of a ventilation unit in differentconfigurations for different buildings.